Comparing In-Person, Standard Telehealth, and Remote Musculoskeletal Examination With a Novel Augmented Reality Exercise Game System: Pilot Cross-Sectional Comparison Study - Richard Wu; Keerthana Chakka; Sara Belko; Ninad Khargonkar; Kevin Desai; Balakrishnan Prabhakaran; Thiru Annaswamy (JMIR Serious Games)
Abstract BackgroundCurrent telemedicine technologies are not fully optimized for conducting physical examinations. The Virtual Remote Tele-Physical Examination (VIRTEPEX) system, a novel proprietary technology platform using a Microsoft Kinect-based augmented reality game system to track motion and estimate force, has the potential to assist with conducting asynchronous, remote musculoskeletal examinations. ObjectiveThis pilot study evaluated the feasibility of the VIRTEPEX system as a supplement to telehealth musculoskeletal strength assessments. MethodsIn this cross-sectional pilot study, 12 study participants with upper extremity pain and/or weakness underwent strength evaluations for four upper extremity movements using in-person, telehealth, VIRTEPEX, and composite (telehealth plus VIRTEPEX) assessments. The evaluators were blinded to each other’s assessments. The primary outcome was feasibility, as determined by participant recruitment, study completion, and safety. The secondary outcome was preliminary evaluation of inter-rater agreement between in-person, telehealth, and VIRTEPEX strength assessments, including κ statistics. ResultsThis pilot study had an 80% recruitment rate, a 100% completion rate, and reported no adverse events. In-person and telehealth evaluations achieved highest overall agreement (85.71%), followed by agreements between in-person and composite (75%), in-person and VIRTEPEX (62.5%), and telehealth and VIRTEPEX (62.5%) evaluations. However, for shoulder flexion, agreement between in-person and VIRTEPEX evaluations (78.57%; κ=0.571, 95% CI 0.183 to 0.960) and in-person and composite evaluations (78.57%; κ=0.571, 95% CI 0.183 to 0.960) was higher than that between in-person and telehealth evaluations (71.43%; κ=0.429, 95% CI −0.025 to 0.882). ConclusionsThis study demonstrates the feasibility of asynchronous VIRTEPEX examinations and supports the potential for VIRTEPEX to supplement and add value to standard telehealth platforms. Further studies with an additional development of VIRTEPEX and larger sample sizes for adequate power are warranted.